ANALISIS EKSERGI PENYIMPANAN PANAS UNTUK SISTEM PENGERINGAN BERENERGI SURYA - Armansyah H Tambunan; Kamaruddin Abdullah; Binsar Nababan (PERTETA, 2006)
ABSTRACT This paper is devoted to discuss the exergy analysis on the utilization of heat storage for a solar drying system. The heat was stroad in the from of sensible heat using pebble bed as the medium. For the analysis , an exergy balance model was developed from the system’s heat balance. The results show that the minimum value of exergy destruction ratio was obtained within two hours after the process was started. The minimum ratio expresses the most effective operation of the stroge system. Upon performing the simulation study, it was found that the number of transfer unit (NTU) influen the change in exergy destruction ratio, with anoptimal value could be in the range of 0,5 to 0,8. Within the NTU range, the ratio of exergy destruction was found to be 0,85. It means that only 15% of the exergy gained from the solar collector can be transferred to the heat stroge medium. The other part of the exergy could be transferred to the drying room or destructed during the process. In order to obtain a more comprehensive understanding on the exergy flow of the system, there necessary an exergy analysis on the drying system. Keyword: sensible heat storage, exergy destruction ratio, number of transfer unit pebble bed Diterima: 24 Agustus 2006; Disetujui: 14 Nopember 2006